Engaging Haydn culture, context, and criticism - Hunter, Mary Kathleen 1951-; Will, Richard James (Cambridge Cambridge University Press, 2012)
"Haydn is enjoying renewed appreciation as one of the towering figures of Western music history. This lively collection builds upon this resurgence of interest, with chapters exploring the nature of Haydn's invention and the cultural forces that he both absorbed and helped to shape and express. The volume addresses Haydn's celebrated instrumental pieces, the epoch-making Creation and many lesser-known but superb vocal works including the Masses, the English canzonettas and Scottish songs and the operas L'isola disabitata and L'anima del filosofo. Topics range from Haydn's rondo forms to his violin fingerings, from his interpretation of the Credo to his reading of Ovid's Metamorphoses, from his involvement with national music to his influence on the emerging concept of the musical work. Haydn emerges as an engaged artist in every sense of the term, as remarkable for his critical response to the world around him as for his innovations in musical composition"-- Provided by publisher. "It is finally and mercifully a boring truism to say that Haydn's reputation no longer rests on his position as precursor to Mozart and Beethoven or as the jolly but superficial "Papa" Haydn. It is also a truism of introductions to Haydn volumes to say that the composer is finally getting both the quantity and quality of attention he richly deserves. However, since one of the qualities of a truism is truth, it is worth pointing out that this volume builds on a scholarly tradition spanning the second half of the twentieth century and showing no signs of diminishing today, which contests the still-extant and historically incomplete (at best) tendency to think of the eighteenth century as the century of Bach and Mozart rather than of Handel and Haydn"-- Provided by publisher
Introduction / Mary Hunter and Richard Will -- Part I : Cultures of vocal music -- Fantasy island : Haydn's metastasian "reform" opera / Elaine Sisman -- Haydn invents Scotland / Richard Will -- Haydn's English canzonettas in their local context / Katalin Komlos -- Revolution, rebirth and the sublime in Haydn's L'anima del filosofo and The Creation / Caryl Clark -- "Achieved is the glorious work" : The Creation and the choral work concept / Nicholas Mathew -- Part II Analytical readings and rereadings -- Imagination, continuity, and form in the first movements of Haydn's opus 77 quartets / Lewis Lockwood -- Does Haydn have a "C-minor mood"? / Jessica Waldoff -- Form, rhetoric, and the reception of Haydn's rondo finales / Michelle Fillion -- Haydn and the Metamorphoses of Ovid / Pierpaolo Polzonetti -- Credo ut intelligam : Haydn's reading of the Credo text / Tom Beghin -- Part III : Performance -- Haydn's string quartet fingerings : communications to performer and audience / Mary Hunter -- Haydn's orchestras and his orchestration to 1779, with an excursus on the times-of-day symphonies / Neal Zaslaw.
Includes bibliographical references (pages 322-343) and index.
Keywords: Hayd, Joseph -- 1732-1809 -- Criticism and interpretation